Math Learning With Realistic Mathematics Education Approach Based On Open-ended Problems - Khusnul Khotimah; Alimatul Mahmudah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the feasibility and effectiveness of learning mathematics using teaching materials in the form of LKPD with a Realistic Mathematics Education (RME) approach based on open-ended problems. The design used in this research is Research and Development with a development model developed by Dick and Carry. Subjects in this study were students of class X IPA at Al-bairuny Islamic Senior High School in the academic year 2020/2021. Design implementation is using One Group Pretest Posttest Design with instruments in the form of questionnaires and tests. Data on student's understanding of mathematical concepts were collected using instrument tests as many as 5 essay questions. The analysis technique used is descriptive quantitative and qualitative. The results showed that (1) the validation of teaching materials is categorized as valid with an average score of 84,89% based on the expert judgment as well as the percentage of student’s responses to learning media of 80,29% categorized as feasible. (2) the effectiveness of teaching materials to reach the achievement of student’s competence gets an average score of 80,88 of the student learning outcomes and percentage of classical completeness of 89,47% categorized as very good. Based on the results of research findings and discussion, obtained the conclusion that the mathematics LKPD with the Realistic Mathematics Education (RME) approach based on open-ended development is feasible and effective to be used in the teaching and learning process.